(untitled) (CIPEEX, 2025)
Purple Ipê (Handroantus impetiginosus) is popularly known for its various medicinal actions. Some biological activities, including antimicrobial ones, have already been tested and found in the plant’s components, notably lapachol and other secondary metabolites such as coumarins, flavonoids, and tannins. This study aimed to evaluate the antibiotic activity of the ethanolic extract of Handroantus impetiginosus bark against strains of Staphylococcus Aureus, Staphylococcus agalactiae, Streptococcus pyogenes, Enterococcus faecalis, Escherichia Coli, Pseudomonas aeruginosa, Salmonela typhimurium and Klebsiella pneumoniae carbapenemase using the Minimum Inhibitory Concentration (MIC) technique. The results suggest that the plant’s ethanolic extract has better antimicrobial potential against Gram-positive bacterial strains.